A broad Iceland plume associated with two phase transitions at the 660 km discontinuity: Constraints from receiver functions - Wang, Dan (Scholars' Mine, 2020)
"In spite of the fact that Iceland is frequently regarded as the archetypal example of mantle plumes, the existence, depth extent, origin, dimension and excess temperature of the hypothesized plume remain enigmatic and hotly debated. The controversy mostly originates from the limited vertical resolution of seismic tomography techniques and the associated uncertainty in the depth and lateral extents of the lower wavespeed anomaly. Here we utilize a robust receiver-function-based technique to image the topography of the 410 and 660 km discontinuities bordering the mantle transition zone beneath Iceland and surrounding oceanic regions, and construct thermal and seismic wavespeed models of the upper mantle and mantle transition zone based on the observations. The preferred model invokes a broad plume laterally extending ~1000 km originated from the lower mantle. The dominant phase transition across the 660-km discontinuity is the post-spinel transition in the peripheral area, but becomes the post-garnet transition in the central portion of the plume stem due to the excessive temperature anomaly. This phase transition variation significantly enlarges the plume dimension and enhances upwelling of plume material"--Abstract, page iv.